Algorithms for Quantification Evaluation Criteria for the Effect of Integration of a Distribution System with Distributed Generation Units - شعبان, فيصل; خير بك, طارق; رزوق, سنان (Latakia University Journal -Engineering Sciences Series, 2020)
The expansion of electrical energy loads led to the expansion of the electricity network, and the increased transmitted capacity caused an increase in the losses of electrical energy as well as the difference in the voltage levels and this represents a permanent problem for the performance of the electrical distribution system that must be dealt with. In the distribution system, as well as maintaining the levels of effort when transferring a large amount of energy, one of these methods was the use of small energy sources (called distributed generation) which include renewable energy sources and others in distribution systems and are closer to the loads. Distributed generation has direct effects on the parameters of voltage and power flow when integrated with the network, and to verify these effects it was necessary to make adjustments to the traditional algorithms adopted in methods of analyzing power flow as the best tool to evaluate the technical performance of electrical networks with distributed generation in the steady state, this research begins Defining distributed generation, classifying its patterns and methods of integrating its units with the distribution system, then provides a full explanation of the quantitative evaluation criteria of the impact of distributed generation on the technical performance of the distribution system and explains the modifications in the technique of analyzing the power flow of distribution systems with the following D distributor, It also aims to find the best capacities and locations for distributed generators that will be applied to distribution systems to achieve the lowest electrical loss and improve the voltage by setting quantitative evaluation algorithms for the effect that the distribution system integrates with distributed generation units.